Bus station mystery. - Warner, Gertrude Chandler, 1890-1979 (Warner, Gertrude Chandler, 1890-1979. Boxcar children mysteries., 1974)
The Alden children, isolated in a storm at a small bus station, are led into a mystery centering on a polluted river.